DEVELOPMENT DIRECTIONS OF COOPERATION BASED ON INDUSTRIAL CLUSTERS - Sobitova Rano Solidjonovna (Web of Journals Publishing, 2024)
The article highlights the issue of how the development of production clusters that process local raw materials is one of the ways to mobilize resources to increase economic growth in the regions.
Keywords: localization, industrial clusters, technological parks, intersectoral cooperation, import substitution.